"That's my country belonging to me" : Aboriginal land tenure and dispossession in nineteenth century Western Victoria ... - Clark, Ian D. (Monash University, 2025)
Content advice: Aboriginal and Torres Strait Islander People are advised that this material contains content that may be distressing and is culturally sensitive. It contains language, terms, and descriptions that are a product of their time and would now be considered offensive.ICIP statement: This material contains Indigenous Cultural and Intellectual Property (ICIP) of Australian First Nations Peoples. Restrictions on access and use of this material may apply.A historical geography of dispossession in which social organisation boundaries and nomenclature of clans of Dhauwurd wurrung, Djab wurrung, Djadja wurrung, Djargurd wurrung, Gadabanud, Girai wurrung, Gulidjan, Jardwadjali, Watha wurrung and Wergaia were reconstructed from historical sources, mostly Robinson papers and some linguistic comparison; documented effects of dispossession on clan estates from European occupation of land giving examples of resulting negative and positive race relations and removal of clans to Lake Condah and Framlingham; ...